g-Irradiation Activates Biochemical Systems: Induction of Nitrate Reductase Activity in Cajanus cajan in vitro and in vivo Conditions - Neelam, Darakshanda; Subhan, Shahnaz; Husain, S.A.; Mahmooduzaffar (Asian Journal of Chemistry, 2012)
g-Irradiation induces various physiological and biochemical alterations in plants. g-Irradiation lead to activation of biochemical system in Cajanus cajan when subjected to absorbed doses 30Gy, 50Gy, 100Gy, 150Gy and 200Gy under in vivo and in vitro conditions. Nitrate reductase activity enhanced significantly (p < 0.05) with increasing doses of g-radiation under both in vitro and in vivo conditions. g-Irradiation induced high levels of nitrate reductase activity in regenerative callus, in vitro raised micoshoots and also in vivo grown leaves whereas a reverse effect was seen in case of nitrate content. Nitrate content declined significantly with increasing doses of g-radiation under both in vitro and in vivo conditions. However, absorbed doses 30Gy and 50Gy of g-rays had a stimulatory effect on nitrate accumulation.